Penggunaan Media Sosial Sebagai Media Pembelajaran English For Hospitality - Ni Ketut Sri Rahayuni (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Social media (social media) has now become a part of the life of Indonesian people who are very phenomenal. Various kinds of advantages and conveniences are offered to interact with everyone both in terms of business even from various circles. Not only that, with the development of internet use and communication technology devices such as smartphones that are increasingly advanced, it has become one of the drivers of the growth of new networking sites that offer friends and information online. Social media has also become the backbone as a means of communication in this digital century. This study aims to determine students' perceptions about the extent of the use of social media in helping them learn English. English that is expected to be understood and learned is English in hospitality and also in advertising language. English that is expected to be understood and learned is English in hospitality and also in advertising language. This research is important to find out how students perceive the effectiveness of using social media to support their learning and understanding and creativity in the field of English for Hospitality and in compiling advertising language. A total of 50 students from the English Literature study program of Udayana University will be used as data sources in conducting this research. This research will use qualitative methods with a case study design. The use of questionnaires as well as semi-structured interviews will be carried out in collecting data. In analyzing the data will use a basic statistical model of the results of questionnaires on students. Meanwhile, the results of the interview data will be analyzed with the Flow model from Miles and Huberman.